2015
DOI: 10.5941/myco.2015.43.1.31
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of ε-COP in the COPI Vesicular Coat Reduces Cleistothecium Production inAspergillus nidulans

Abstract: We have previously isolated ε-COP, the α-COP interactor in COPI of Aspergillus nidulans, by yeast two-hybrid screening. To understand the function of ε-COP, the aneA+ gene for ε-COP/AneA was deleted by homologous recombination using a gene-specific disruption cassette. Deletion of the ε-COP gene showed no detectable changes in vegetative growth or asexual development, but resulted in decrease in the production of the fruiting body, cleistothecium, under conditions favorable for sexual development. Unlike in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
1
1
1
Order By: Relevance
“…is one of the medicinal fungi traditionally used by Europeans to cure pyretic diseases, coughs, gastric cancer, and rheumatism ( Ríos et al., 2012 ). In accordance with previous studies, submerged mycelial cultured Laetiporus sulphureus has been reported to produce functional polysaccharides ( Jayasooriya et al., 2011 , Lung and Wei, 2011 ) as well as mycophenolic acids ( Fan et al., 2014 ) and being able to attenuate the excessive immune activation of the selected cells without causing cytotoxicity ( Saba et al., 2015 , Wang et al., 2017 ). Furthermore, our previous study showed that solid-state–fermented L. sulphureus can modulate lipopolysaccharide ( LPS )–triggered inflammation process involving TLR4 and NF-κB mediation in chicken peripheral blood monocytes ( Lin et al., 2019 ).…”
Section: Introductionsupporting
confidence: 88%
See 1 more Smart Citation
“…is one of the medicinal fungi traditionally used by Europeans to cure pyretic diseases, coughs, gastric cancer, and rheumatism ( Ríos et al., 2012 ). In accordance with previous studies, submerged mycelial cultured Laetiporus sulphureus has been reported to produce functional polysaccharides ( Jayasooriya et al., 2011 , Lung and Wei, 2011 ) as well as mycophenolic acids ( Fan et al., 2014 ) and being able to attenuate the excessive immune activation of the selected cells without causing cytotoxicity ( Saba et al., 2015 , Wang et al., 2017 ). Furthermore, our previous study showed that solid-state–fermented L. sulphureus can modulate lipopolysaccharide ( LPS )–triggered inflammation process involving TLR4 and NF-κB mediation in chicken peripheral blood monocytes ( Lin et al., 2019 ).…”
Section: Introductionsupporting
confidence: 88%
“…(2017) as being able to inhibit LPS-induced activation of NF-κB pathways and downregulate the inflammatory response in RAW 264.7 cells. Similarly, Saba et al. (2015) reported that acetyl eburicoic acid from LS can reduce the proinflammatory cytokines secreted by LPS-induced RAW 264.7 cells.…”
Section: Discussionmentioning
confidence: 87%
“…It has been proposed that the -COP CTD/-COP heterodimer projects away from the COPI coat to mediate the interaction of the COPI vesicle with the acceptor Dsl1 tethering domain in the ER (Hsia and Hoelz, 2010). However, we note that -COP is the only COPI subunit that is not essential in S. cerevisiae and that ablation of A. nidulans -COP does not affect vegetative growth either (Kang et al, 2015), suggesting that the conditionally lethal phenotype of copA1ts does not result from its effects on the -COP CTD/-COP heterodimer, but is rather an effect on COPI as a complex.…”
Section: Molecular Characterization Of Copa1tscontrasting
confidence: 73%